Absence of Vaccine-enhanced Disease With Unexpected Positive Protection Against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by Inactivated Vaccine Given Within 3 Days of Virus Challenge in Syrian Hamster Model. (30th January 2021) - Li, Can; Chen, Yan-Xia; Liu, Fei-Fei; Lee, Andrew Chak-Yiu; Zhao, Yan; Ye, Zhan-Hong; Cai, Jian-Piao; Chu, Hin; Zhang, Rui-Qi; Chan, Kwok-Hung; Chiu, Kelvin Hei-Yeung; Lung, David Christopher; et al.
Abstract: Background: Mass vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is ongoing amidst widespread transmission during the coronavirus disease-2019 (COVID-19) pandemic. Disease phenotypes of SARS-CoV-2 exposure occurring around the time of vaccine administration have not been described. Methods: Two-dose (14 days apart) vaccination regimen with formalin-inactivated whole virion SARS-CoV-2 in golden Syrian hamster model was established. To investigate the disease phenotypes of a 1-dose regimen given 3 days prior (D-3), 1 (D1) or 2 (D2) days after, or on the day (D0) of virus challenge, we monitored the serial clinical severity, tissue histopathology, virus burden, and antibody response of the vaccinated hamsters. Results: The 1-dose vaccinated hamsters had significantly lower clinical disease severity score, body weight loss, lung histology score, nucleocapsid protein expression in lung, infectious virus titers in the lung and nasal turbinate, inflammatory changes in intestines, and a higher serum neutralizing antibody or IgG titer against the spike receptor-binding domain or nucleocapsid protein when compared to unvaccinated controls. These improvements were particularly noticeable in D-3, but also in D0, D1, and even D2 vaccinated hamsters to varying degrees. No increased eosinophilic infiltration was found in the nasal turbinate, lung, and intestine after virus challenge. Significantly higher serum titer of fluorescent foci microneutralization inhibition antibody was detected in D1 and D2 vaccinated hamsters at day 4 post-challenge compared to controls despite undetectable neutralizing antibody titer. Conclusions: Vaccination just before or soon after exposure to SARS-CoV-2 does not worsen disease phenotypes and may even ameliorate infection. Abstract : Formalin inactivated SARS-CoV-2 vaccine given within 3 days of live SARS-CoV-2 exposure does not worsen disease phenotypes, and may even ameliorate infection with detectable neutralizing antibodies in a Syrian hamster model.